STUDI KASUS : DISIPLIN KERJA DOSEN DALAM PROSES BELAJAR MENGAJAR - Deltari Novitasari (LPPM STIKES BHAKTI HUSADA BENGKULU, 2019)
Lecturers at universities have a big burden in creating generations of students to compete in the current era of 4.0. Lecturer work discipline that will both accelerate the achievement of educational goals, and lack discipline will hamper the achievement of educational goals. Based on observations at STIkes Bhakti Husada Bengkulu there were still found lecturers who carried out their duties with low discipline. This type of research is quantitative, using descriptive analysis and data collection methods using questionnaires, with a sample of 40 people. The results of the study showed that the lecturers' employment was very good category (4.58). Suggestions, lecturers should maintain discipline. Key Words : Dicipline, Lectures, Learning